A history of European literature : the West and the world from antiquity to the present (Oxford university press, 2017)
Walter Cohen argues that the history of European literature and of each of its standard periods can be illuminated by comparative consideration of the different literary languages within Europe and of the relationship of European literature to world literature. The global history of literature from the ancient to the present can be divided into five main, overlapping stages. European literature emerges from world literature before the birth of Europe-during Antiquity, whose Classical languages are the heirs to the complex heritage of the Old World. That legacy is later transmitted by Latin to the various vernaculars. The distinctiveness of this process lies in the gradual displacement of Latin by a system of intravernacular leadership dominated by the Romance languages. An additional unique feature is the global expansion of Western Europe's languages and characteristic literary forms, especially the novel, beginning in the Renaissance. This expansion ultimately issues in the reintegration of European literature into world literature, in the creation of today's global literary system.